2014
DOI: 10.1177/1470595814522772
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of citizenship behavior in Arab employees in Kuwait

Abstract: This study identifies antecedents of two specific dimensions of organizational citizenship behavior, altruism (OCBI) and civic virtue (OCBO), in a sample of Arab employees working in Kuwait. Results indicate that a collectivist orientation is a significant predictor of altruism and that procedural justice and job satisfaction are significant predictors of civic virtue. Additionally, respondents indicate that both altruism and civic virtue behaviors are more likely to be perceived as in-role than extra-role beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
(131 reference statements)
0
8
0
Order By: Relevance
“…Similarly, Elamin and Tlaiss (2015) studied the same topic in a wide range of organizations and industries to determine if interactional justice has a major effect on the different sub-dimensions of OCB: civic virtue, conscientiousness, altruism, courtesy and sportsmanship. However, Daly et al (2014) found that distributive justice was not significantly related to two dimensions of OCB, altruism and civic virtue, in mid-sized business organizations in Kuwait. Daly et al (2014) also reported that only procedural justice dimensions for OJ can increase both altruism and courtesy dimensions of OCB.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Elamin and Tlaiss (2015) studied the same topic in a wide range of organizations and industries to determine if interactional justice has a major effect on the different sub-dimensions of OCB: civic virtue, conscientiousness, altruism, courtesy and sportsmanship. However, Daly et al (2014) found that distributive justice was not significantly related to two dimensions of OCB, altruism and civic virtue, in mid-sized business organizations in Kuwait. Daly et al (2014) also reported that only procedural justice dimensions for OJ can increase both altruism and courtesy dimensions of OCB.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 98%
“…However, Daly et al (2014) found that distributive justice was not significantly related to two dimensions of OCB, altruism and civic virtue, in mid-sized business organizations in Kuwait. Daly et al (2014) also reported that only procedural justice dimensions for OJ can increase both altruism and courtesy dimensions of OCB.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 98%
“…Furthermore other researchers defined OCB has a voluntary helping behavior that is discretionary and promotes the organization effective functioning without expecting direct or explicit reward or recognition from the organization (Daly, Owya-Hosseini and Alloughani, 2014). Bandurs and Lyons (2012) also explained the concept of voluntary helpful behavior, the research was achieved in Maryland on a small homogenous group, and results have shown that voluntary helpful behavior is less significant than providing training and development to homogenous group.…”
Section: Definition Of Organizational Citizenship Behaviourmentioning
confidence: 99%
“…Conscientiousness is a behavior that can easily be recognized by managers as employees are predisposed to be supportive, committed and fair in their act (Daly, Owya-Hosseini and Alloughani, 2014). It is one of the organizational advantages as in it contributes to employees engagement in establishing a working relationship with coworkers.…”
Section: Conscientiousnessmentioning
confidence: 99%
See 1 more Smart Citation